3(x-1)-2(2x+1)=8(x+1)

Simple and best practice solution for 3(x-1)-2(2x+1)=8(x+1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(x-1)-2(2x+1)=8(x+1) equation:


Simplifying
3(x + -1) + -2(2x + 1) = 8(x + 1)

Reorder the terms:
3(-1 + x) + -2(2x + 1) = 8(x + 1)
(-1 * 3 + x * 3) + -2(2x + 1) = 8(x + 1)
(-3 + 3x) + -2(2x + 1) = 8(x + 1)

Reorder the terms:
-3 + 3x + -2(1 + 2x) = 8(x + 1)
-3 + 3x + (1 * -2 + 2x * -2) = 8(x + 1)
-3 + 3x + (-2 + -4x) = 8(x + 1)

Reorder the terms:
-3 + -2 + 3x + -4x = 8(x + 1)

Combine like terms: -3 + -2 = -5
-5 + 3x + -4x = 8(x + 1)

Combine like terms: 3x + -4x = -1x
-5 + -1x = 8(x + 1)

Reorder the terms:
-5 + -1x = 8(1 + x)
-5 + -1x = (1 * 8 + x * 8)
-5 + -1x = (8 + 8x)

Solving
-5 + -1x = 8 + 8x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-8x' to each side of the equation.
-5 + -1x + -8x = 8 + 8x + -8x

Combine like terms: -1x + -8x = -9x
-5 + -9x = 8 + 8x + -8x

Combine like terms: 8x + -8x = 0
-5 + -9x = 8 + 0
-5 + -9x = 8

Add '5' to each side of the equation.
-5 + 5 + -9x = 8 + 5

Combine like terms: -5 + 5 = 0
0 + -9x = 8 + 5
-9x = 8 + 5

Combine like terms: 8 + 5 = 13
-9x = 13

Divide each side by '-9'.
x = -1.444444444

Simplifying
x = -1.444444444

See similar equations:

| 2(x+51)+4x=180 | | 8b-5(6+b)=-4(6b-6) | | 1+2x=16-3x | | m/3-2=8 | | 5x-10=22 | | 5(x-3)+57=-2x | | -4(4Y-10)-Y=-4(Y-5) | | x-9=x-x | | 0.85x+0.05(14-x)=0.10(-121) | | 0.75y-30=-16.5 | | 7(2a-6)-5= | | 3(X-15)=12X | | 3[4-8+4(2+5)]= | | 2x+20-20=180 | | 2a-5=9a+9 | | -1.3x=5.9 | | 10X+19=3(3X+5) | | 2x-1+x+47=180 | | r+13=3 | | n^2-10-3n=0 | | 5x+4x+11=180 | | 9X-3X+5=X-2+7 | | 7x+2-10x=-5-12x+2 | | X(x+7)=144 | | 12=2(3)+7 | | 39+8a=-591-6a | | 15c-15=4c+5 | | x^2-30x=-56 | | 67+c=-789 | | -4.6=3.4-2y | | (a+9)+7bi=9-6i | | 7Y+10=3Y-2 |

Equations solver categories